Understanding Professional Discretion by Principals in Managing Drugs in Gauteng Province schools in South Africa - Kgwete Ephraim Matala (Discourse and Communication for Sustainable Education)
Principals are faced with some frustrating situations from time to time in their line of duty in which they must make a variety of decisions affecting their students. This study argues that principals need to understand how to apply professional discretion in their practice and be accountable for their judgements and decisions to avoid the notion of negligence when managing drugs in schools. Educational institutions are viewed as places where stakeholders, especially principals and teachers are recognized for their work as knowledge producers and key figures in educational and social transformation. Appropriate exercise of professional discretion in the management of drugs in schools can play a role towards social transformation and sustainable development. Target 4.8 of the Sustainable Development Goal 4 envisages to build and upgrade inclusive and safe schools. School principals are responsible for maintaining a safe, secure and orderly school environment. A qualitative research design was employed to collect data from secondary school principals in quintiles 1 to 3 (disadvantaged schools) in the Gauteng Province of South Africa. The study adopted an interpretivist paradigm. Data collection was done by the means of qualitative data collection techniques, in which semi-structured interviews supported by document analysis were employed. This study revealed that some principals make professional discretions that are influenced by emotions and violate the rights of learners in the process while managing drugs in schools.